O prawdzie – II hermetyczny fragment Stobajosa. Przekład i komentarz - Tylak, Aneta (Collectanea Philologica, 2023)
Stobaeus’s Anthology contains – among others – the Hermetic fragments attributed to Hermes Trismegistos. In the twentieth century French scholar, A.-J. Festugière added 29 Hermetic excerpts of Stobaeus in the Corpus Hermeticum. The Article is a translation of excerpt II of Stobaeus with commentary.